AI is upending the porn industry. (Economist, 2025)
The article offers a glimpse of how artificial intelligence (AI) will upend the pornography industry. Topics discussed include the rise of AI porn generators and nudify apps, the need for adult platforms to decide whether to allow AI-generated content, concerns about AI-generated content showing the sexual abuse of children being shared online, strangulation practices in mainstream pornography and in the discourse on sexuality, deepfake technology and policing of Internet for erotic content.